ANALISIS FAKTOR PENYEBAB TURNOVER SALES PADA MASA PROBATION DI PT. HADJI KALLA TOYOTA - Putri, Balqis Maharani; Ghina Nailah; Ratu Bilqis Emelqis Ma’arif; Novi Yanti Pratiwi (JURNAL ILMIAH NUSANTARA, 2025)
Early Turnover is a strategic issue in human resource management because it impacts team stability and organizational effectiveness. This study aims to explore the causes of high Turnover among sales interns at PT Hadji Kalla Toyota, especially those who left before three months of employment. The study used a descriptive qualitative approach with an interview method with 20 former employees who resigned in the period September to December 2024. The analysis showed six main factors causing early Turnover, namely high workload, lack of career development opportunities, personal reasons, family conditions, inadequate reward system, and unsupportive work environment. These factors are interrelated and the majority come from internal aspects of the company. The findings are expected to serve as a basis for formulating more effective and sustainable employee recruitment, training and retention strategies